(untitled) (Nuovi Autoritarismi e Democrazie: Diritto, Istituzioni, Società (NAD-DIS), 2022)
Departing from the direct testimonies gathered in Afghanistan during over 20 years of fieldwork, the paper offers an overview of Afghan women’s resistance, especially following the experience of the RAWA association, in their fight against all the oppressive regimes that have featured Afghanistan’s history, from the resistance against the Red Army, to that against the United State’s and NATO invasion, to the restored Taliban regime. The paper, also, focuses on the struggles of the Afghan democratic resistance in the years of the Soviet occupation, which the A. personally witnessed in 1980.